THE REASONS FOR DEVELOPMENT OF COMPLICATIONS IN SOFT CONTACT LENSES WEARERS: A QUALITATIVE STUDY - Milosavljević, Miloš; Milosavljević, Jovana; Kočović, Aleksandar; Milentijević, Milica; Janković, Slobodan; Stefanović, Srđan (Medicinski časopis, 2021)
Aims: To determine reasons and their actual role in occurrence of complications in users of soft contact lenses.Methods: This was a qualitative study in which a constructivist grounded theory approach was used to analyse obtained data. The study population consisted of two groups of subjects: 10 students who were identified as users of the soft contact lenses and 4 ophtalmologists. Each of the respondents was provided with a single interview. Based on audio recordings of these interviews appropriate transcripts of conversations were made and analyzed. After elimination of waste words 11 key categories were crystallized.Results: Recommendations of the оphthalmologists perhaps have the decisive role in the formation of attitude that users will have regarding the adequate hygiene of soft contact lenses: hand hygiene, proper cleanliness of storages for soft contact lenses and using the solution in the allotted time are imperative for users of soft contact lenses. Sleeping with soft contact lenses for a long period and more frequently than it was specified in the recommendation of an ophthalmologist is one of the greatest reasons for development symptoms of dry eye, while swimming with soft contact lenses increases risk for the occurrence of eye infections.Conclusion: Main reasons for the occurrence of complications in soft contact lenses users are inadequate hygiene and weakening of compliance of soft contact lenses users over time.
Keywords: soft contact lenses; dry eye; eye infections; ulceration of cornea